A vexing case of non-healing ulcers with interstitial lung disease (Indian Journal of Case Reports, 2024)
Clinically amyopathic dermatomyositis is a subset of dermatomyositis that does not have any clinical evidence of muscle inflammation. Hence, it frequently poses a diagnostic challenge to the clinician. Here, we present a middle-aged farmer who presented only with multiple non-healing ulcers and was eventually found to be having early interstitial lung disease. He was finally diagnosed with anti- melanoma differentiation-associated gene 5 dermatomyositis and was started on aggressive immunosuppressants.